THE EFFECT OF WORK-LIFE BALANCE AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON EMPLOYEE PERFORMANCE AT THE LEBAK REGENCY PERSONNEL AND HUMAN RESOURCE DEVELOPMENT AGENCY - Rozi, Achmad; Nabillah Wondu, Tiara; Harun, Asro (Amal Insani Foundation, 2026)
This study aims to analyze the influence of work-life balance and organizational citizenship behavior on employee performance at the Lebak Regency Personnel and Human Resources Development Agency (BKPSDM). The study used a quantitative approach with a population of 30 employees and saturated sampling techniques. Data were collected through questionnaires and analyzed by multiple linear regression. The results of the study show that work-life balance and organizational citizenship behavior have a positive and significant effect both partially and simultaneously on employee performance. The value of the determination coefficient (R²) of 0.610 or 61.0% indicates that the two variables are able to explain employee performance by 61.0%, while the remaining 39.0% is influenced by other factors outside of this study. Partially, organizational citizenship behavior has a more dominant influence than work-life balance in improving employee performance.